On the interplay between Keynesian and supply side economics - Marika Karanassou; Dennis J. Snower (Institute for Advanced Studies (IHS), 2007)
Conventional wisdom suggests that nominal, demand-side shocks have only temporary effects on real macroeconomic magnitudes and that the duration of their effects depends on the degree of nominal inertia. It is also argued that, in the absence of unit roots, temporary supply-side shocks also have only temporary real affects and that the duration of these effects depends on the various sources of real inertia. Our analysis indicates that there is a potentially important interplay between real and nominal inertia in generating the persistent effects of real and nominal shocks. In this sense, then, Keynesian and supply-side economics are mutually interdependent. Our analysis has identified circumstances when real and nominal inertia are complementary in generating real and nominal persistence. Here, we argue, lies a potentially crucial, but as yet largely unexplored, set of determinants of the effectiveness of Keynesian and supply-side economic policies.
Keywords: J64; J21; J68; J23; J31; 330; Unemployment; employment; wage setting; labour force participation; labour market dynamics; unemployment persistence; Beschäftigung; Arbeitslosigkeit; Lohnbildung; Arbeitsangebot; Arbeitsmarkt; Langzeitarbeitslosigkeit; Keynesianismus; Angebotsorientierte Wirtschaftspolitik; Wirtschaftstheorie